Vision based solar tracking system for efficient energy harvesting - Kanhaiya Kumar; Lokesh Varshney; A. Ambikapathy; Inayat Ali; Ashish Rajput; Anant bhatnagar; Sajal omar (International Journal of Power Electronics and Drive Systems (IJPEDS), 2021)
Electricity is a major source of energy for fast growing population and the use of nonrenewable source is harmful for our environment. This reason belongs to devastating of environment, so it is required to take immediate action to solve these problems which result the solar energy development. Production of a solar energy can be maximizing if we use solar follower. The major part of solar panels is microcontroller with arrangement of LDR sensor is used to follow the sun, where the sensors is less efficient to track the sun because of the low sensitivity of LDR. We are proposing a method to track sun more effetely with the help of both LDR sensors and image processing. This type of mechanism can track sun with the help of image processing software which combines both result of sensors and processed sun image to control the solar panel. The combination of both software and hardware can control thousands of solar panels in solar power plants.